Effect of electrical stimulation and hot boning on the eating quality of Gannan yak longissimus lumborum. (February 2016) - Lang, Yumiao; Sha, Kun; Zhang, Rui; Xie, Peng; Luo, Xin; Sun, Baozhong; Li, Haipeng; Zhang, Li; Zhang, Songshan; Liu, Xuan
Abstract: The objective of this study was to evaluate the effects of electrical stimulation (ES) versus non-electrical stimulation (NES) and type of boning (hot versus cold) on the eating quality of Gannan yak longissimus lumborum. Eighteen Gannan yak bulls were randomly divided into two groups: ES and NES. Hot boning (HB) and cold boning (CB) were applied to the left and right side of the carcasses, respectively. All of the four treatments missed the "ideal" pH/temperature window. HB reduced the rate of pH decline, decreased meat tenderness and water holding capacity. ES increased the rate of pH decline and improved yak meat tenderness ( P < 0.05); however, ES explained only 1% of the variation in WBSF. HB and ES had no significant effects on cooking loss, L* or b* values of yak meat. Postmortem aging increased yak meat tenderness and improved meat color parameters. HB had negative effects on yak meat quality, while ES could not reverse these deleterious effects. Highlights: HB yak meat quality can be improved by ES and postmortem aging. HB treatment decreased the tenderness and water holding capacity of yak meat. ES improved HB and CB yak meat tenderness, but the effect was quite small. Postmortem aging increased yak meat tenderness and improved meat color parameters.